Characteristics of Disease Profile of Hospitalized Patients Referred to the Department of Cardiology in a Tertiary Care Hospital (Bangladesh Heart Journal, 2019)
Objectives: Cardiology consultation for hospitalized patients is a common and sometimes mandatory practice in every country. This is because of increased morbidity and mortality of cardiac cases that also has other co-morbidities. We conducted this study to know the pattern of disease profile and the idea of requesting doctors about the cardiac diseases from the cases they referred to the department of Cardiology.Methods: This prospective observational study was carried out in BIRDEM General Hospital, Shahbag, Dhaka from July to December 2017. We followed every case till the final and confirmed diagnoses were made. All the relevant collected data were compiled on a master data sheet. All findings were expressed as frequency with percentage and analysis were done using SPSS for windows version 22.0.Results: This study revealed that majority of the referred cases to the department of cardiology was routine (84.4%) and non-cardiac (57%). Non-cardiac cases were referred mainly for the fitness of general anesthesia (GA) (18.4%). But among the critical cases (14.0%), mostly were cardiac (9.1%). Among all the cardiac cases, Hypertension (8.8%) got the highest referral followed by Acute Myocardial Infarction (AMI) (3.8%) and Dilated Cardiomyopathy (DCM) (3.8%).Conclusions: Hospitalized patients were referred to the department of Cardiology differs according to the requesting unit. The surgical units referred their cases to get the cardiac clearance for a major surgery and the medical units referred for typical cardiac emergencies like AMI.Bangladesh Heart Journal 2019; 34(1) : 1-4